1999
DOI: 10.1046/j.1365-3180.1999.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐to‐seed allelopathic effects between two invaders of burned Pampa grasslands

Abstract: The establishment of Lotus tenuis can interfere with colonization by Carduus acanthoides during the early post‐burn recovery of Flooding Pampa grasslands. The purpose of this research was to determine the potential role of L. tenuis seeds as a source of allelopathic compounds involved in that interaction. Imbibed seeds of L. tenuis and aqueous leachates from them were bioassayed for their ability to inhibit germination and seedling growth of C. acanthoides, both on sterilized filter paper and on pasteurized so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
(16 reference statements)
0
34
0
Order By: Relevance
“…decumbens organs (green leaves, roots and senescent leaves) at different concentrations ( Higashinakasu et al (2004) in seven crop and weed species, and by Laterra and Bazzalo (1999) between two invasive species of the pampa grasslands (Argentina).…”
Section: Resultsmentioning
confidence: 99%
“…decumbens organs (green leaves, roots and senescent leaves) at different concentrations ( Higashinakasu et al (2004) in seven crop and weed species, and by Laterra and Bazzalo (1999) between two invasive species of the pampa grasslands (Argentina).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have found evidence for the existence of 'seed-to-seed' allelopathic effects by seed leachate or root exudates (Liu and Lovett 1993a;Kushima et al 1998;Laterra and Bazzalo 1999;Zhang et al 2011), but in most cases this experimental protocol does not exclude, on one hand, the effect of competition, and on the other hand, the possible effect of volatile organic compounds (VOCs), known to participate in plant communication and interactions (Ninkovic 2003;Kellner et al 2010;Gfeller et al 2013;Fiers et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The OP of all extract concentrations in different organs was in the range of (0.048 to (1.27 bar. In bioassays such as that carried out here, OPs in this range could affect the germination and growth (Laterra & Bazzalo 1999), so we also evaluated the OP effects on the abovementioned parameters of the test species.…”
Section: Plant Materials and Extractionmentioning
confidence: 99%